Der tropisch-konvektive und der außertropisch-advektive Typ der vertikalen Niederschlagsverteilung - Weischet, Wolfgang (ERDKUNDE, 1965)
By means of cross sections it is shown to be a climatological regularity that in tropical mountains an initial increase of total annual rainfall at lower altitudes is succeeded from 1,300 to 1,500 m. above sea level onwards by a continuous precipitation decline with increasing altitude whereas outside the tropics total annual precipitation increases right up to the peak level. Based on observations the following causal relationship has been worked out: Precipitation in tropical low and high lying regions, with mainly convectional cloud formation in both, are derived from two different, mutually independent thermo-dynamic systems; a lower system within the base layer of the troposphere with a high degree of water vapour contents, and an upper system above this base layer possessing low water vapour contents. The high water vapour contents of the lower system of tropical air masses is responsible for the fact that most of the rain in tropical lowlands is derived from warm water clouds (Cu cong.) whose upper limit of 2,800?3,000 m. is determined by the quasi-permanent peplopause (Schneider-Carius). In contrast occurrence of noteworthy precipitation outside the tropics normally presupposes the destruction of the base layer and formation of nimbo-stratus or cumulo-nim bus clouds reaching up to considerable altitudes. In cases where cyclonal conditions are responsible for the rise of air masses, warm air of high water vapour contents occurs mainly in the upper layers of the troposphere, thus in cases of substantial precipitation the otherwise usual decrease of water vapour contents with increasing altitude is temporarily even reversed.